Introduction - Casey, Christine (Four Courts Press, 2019)
The Museum Building of Trinity College Dublin is an acknowledged masterpiece of Gothic revival architecture and the single-most influential building of the Victorian period in Ireland. Its genesis and erection owe a great deal to initiatives that sought to improve exploitation of Ireland’s natural resources, and to enhance the abilities of craftsmen through education and practice. Without such developments it is unlikely that this building would have been conceived and realized.
The Museum Building of Trinity College Dublin: a model of Victorian craftsmanship
Keywords: Making Ireland; Irish and British History 1500-1800